2019
DOI: 10.2337/db19-105-lb
|View full text |Cite
|
Sign up to set email alerts
|

105-LB: Does HbA1c Accurately Predict Time-in-Range?

Abstract: Background: Onduo’s Virtual Diabetes Clinic (VDC) incorporates a continuous glucose monitor (CGM), telemedicine, and a coaching app into the management of patients with type 2 diabetes (T2D). A recent meta-analysis of studies involving CGMs (Vigersky & McMahon 2019) showed HbA1c and time in range (%TIR) are strongly correlated. Methods: All patients in the program with CGM usage in the 45 days prior to a follow-up HbA1c were analyzed. Mean HbA1c and %TIR were added to the previously publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…When FGM and rtCGM groups are considered, the predicted values for A1C=7.5% (58 mmol/mol) are TIR=54% and TIR=60%, respectively, while the prediction interval is 33–73 in the former case and 42–78 in the latter, which imply a maximum relative difference between true and estimated values of about 37% for FGM and 30% for rtCGM. In turn, this highlights possible limitations of A1C in predicting the TIR percentage accurately and confirms the opportunity of having different models for different patient groups as suggested by some authors, 31 as well as for FGM versus rtCGM devices, due to the statistically significant difference between their OLS regression models.…”
Section: Discussionsupporting
confidence: 77%
“…When FGM and rtCGM groups are considered, the predicted values for A1C=7.5% (58 mmol/mol) are TIR=54% and TIR=60%, respectively, while the prediction interval is 33–73 in the former case and 42–78 in the latter, which imply a maximum relative difference between true and estimated values of about 37% for FGM and 30% for rtCGM. In turn, this highlights possible limitations of A1C in predicting the TIR percentage accurately and confirms the opportunity of having different models for different patient groups as suggested by some authors, 31 as well as for FGM versus rtCGM devices, due to the statistically significant difference between their OLS regression models.…”
Section: Discussionsupporting
confidence: 77%
“…It is estimated that for every 10% change in TIR, there is a corresponding 0.8% change in HbA1c in a mixed population of T1DM and T2DM [ 33 ]. In T2DM, a mean TIR of 84% corresponds with an HbA1c of 7 % [ 34 ]. It is also observed that a mean TIR of > 70% in T2DM of Asian Indians relates to an HbA1c level of <7.5% [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Efforts have been on to correlate the TIR values with that of HbA1c [ 26 ]; however, a uniform correlation coefficient is yet to be derived. Dixon et al in a cohort of 1924 people with T2DM proposed a correlation coefficient of -0.78 [ 27 ]. Kesavadev et al reported that the HbA1c of < 7.5% in Asians corresponds to a TIR value of > 70% [ 28 ].…”
Section: Discussionmentioning
confidence: 99%